Post-traumatic stress disorder in inpatient psychiatry staff: a narrative review - Merritt, Caley; Agyapong, Vincent I. O.; Nkire, Nnamdi (Frontiers in Psychiatry, 2025)
IntroductionHealthcare workers have high rates of post-traumatic stress disorder (PTSD). The aim of this study is to provide a narrative review of the literature on PTSD in psychiatrists, psychiatric nurses, and other healthcare staff working on psychiatric inpatient units.MethodsA search was conducted on MEDLINE for studies in English. Studies were included if they studied a population of inpatient psychiatric staff and had PTSD as an outcome measure. Of the 1487 articles the search returned, 26 were included.ResultsRates of post-traumatic stress ranged from 0% to 24%, depending on the measurement tool. Nurses had higher rates of PTSD compared to other psychiatric unit staff. There was no difference in PTSD prevalence between forensic and non-forensic psychiatric units. There were mixed findings on the association between gender and age and PTSD. Exposure to suicide, verbal aggression, physical violence, and other disturbing patient behaviors were associated with a higher risk of PTSD.ConclusionHigh rates of post-traumatic stress are seen in healthcare workers in inpatient psychiatric settings. More research is needed on interventions to reduce PTSD in this population.